PARADOKS ADOPSI BIM DI INDONESIA: TINJAUAN SISTEMATIS ATAS EFISIENSI, HAMBATAN, DAN IMPLIKASI KEBIJAKAN - I Kadek Badradnyana Wirapraja Mahatama; I Putu Ari Sanjaya; Anak Agung Diah Parami Dewi (Program Studi Magister Teknik Sipil Universitas Udayana, 2025)
The Indonesian construction industry is at a critical juncture, with government mandates officially encouraging the adoption of Building Information Modeling (BIM) to enhance productivity. However, a significant paradox persists: despite strong evidence of BIM's substantial efficiency benefits, its widespread adoption remains slow and fragmented. This study investigates this paradox through a systematic literature review (SLR) of 79 empirical studies conducted within the Indonesian context. The analysis confirms that BIM offers measurable improvements, including up to 50% time savings during the planning phase and significant cost avoidance from rework, amounting to hundreds of millions of rupiah. Conversely, the study identifies a set of deeply rooted systemic barriers, categorized using the Technology–Organization–Environment (TOE) framework. The most prominent barriers include high initial investment costs (Organisational), a severe shortage of skilled professionals (Organisational), and limited market demand from clients (Environmental). The persistence of this paradox is explained by a cyclical reinforcement of these barriers, a dynamic captured by Institutional Theory, which describes how entrenched norms resist innovation, and Technology Adaptation Theory, which highlights the misalignment between global BIM platforms and local standards (SNI). In contrast to pioneer countries like the UK, Indonesia's BIM mandate lacks comprehensive technical standards, resulting in partial implementation. This study proposes a dual-pronged strategy to break the cycle: top-down government intervention through the development of national standards and a localised BIM component library, and bottom up, market-driven adoption of collaborative contracting models such as Integrated Project Delivery (IPD) to align stakeholder incentives.